Determination of phenolic and flavonoid contents, and antioxidant activity for Piper Betle and Leucosyke Capitella using different solvent for extraction - Murni Sundang (Universiti Malaysia Sabah, 2010)
This research was carried out to determine the antioxidant activity of Leucosyke capitella and Piper betle. Petroleum ether, acetone and methanol were used as solvents for extraction. Results indicate that Piper bette has significantly higher antioxidant activity compare to Leucosyke capitella. The capacity of solvents to extract phenolic, flavonoid and tannin for Piper bette and Leucosyke capitella is in the order of acetone> methanol > petroleum ether. The results also show that the total phenolic content for Piper bette and Leucosyke capitella is in the range of 31.25 to 47.48 mg/g and 1.68 to 7.19 mg/g, respectively. For Piper betle, the total flavonoid content is in the range of 29.58 to 46.08 mg/g and for Leucosyke capitella is in the range of 1.08 to 6.83 mg/g. It is also found that Piper betle extracted with methanol has higher antioxidant activity than vitamin E, butylated hydroxytoluene (SHT) and catechin but lower than quercetin.